1990
DOI: 10.1128/jcm.28.9.2117-2119.1990
|View full text |Cite
|
Sign up to set email alerts
|

Detection of herpes simplex virus by the Kodak SureCell Herpes Test

Abstract: The Kodak SureCell Herpes Test Kit (SC-HSV) was evaluated in a high-risk sexually transmitted disease clinic population. A total of 97 lesion specimens (from 94 patients) were tested for the presence of herpes simplex virus by SC-HSV and by spin-amplified tissue culture confirmed by an enzyme immunoassay. The overall sensitivity of SC-HSV compared with that of spin-amplified tissue culture-enzyme immunoassay was 81.1%; the specificity was 100%. For vesicular lesions only, SC-HSV sensitivity was 100%; for nonve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…However, the protocols used in these studies differed so much that appropriate comparisons are difficult. Recently, Dorian et al, using a culture methodology different from the one we use (spin-amplified tissue culture confirmed by enzyme immunoassay) reported a sensitivity and specificity of 100.0 and 100.0%, respectively, for vesicular lesions tested with the Kodak SureCell and a sensitivity and specificity of 75.6 and 100.0%, respectively, for nonvesicular lesions (6). This demonstrates the variability associated with the evaluation of assays assessed by different conventional protocols.…”
mentioning
confidence: 77%
“…However, the protocols used in these studies differed so much that appropriate comparisons are difficult. Recently, Dorian et al, using a culture methodology different from the one we use (spin-amplified tissue culture confirmed by enzyme immunoassay) reported a sensitivity and specificity of 100.0 and 100.0%, respectively, for vesicular lesions tested with the Kodak SureCell and a sensitivity and specificity of 75.6 and 100.0%, respectively, for nonvesicular lesions (6). This demonstrates the variability associated with the evaluation of assays assessed by different conventional protocols.…”
mentioning
confidence: 77%
“…No instrumentation or special transport media, other than viral transport media, are required. Dorian and others suggest that all negative test results should be followed up by inoculation of cell culture (21,22).…”
Section: Herpes Simplexmentioning
confidence: 99%
“…The first reports of the rapid detection of HSV using centrifuged cultures with immune staining were by Gleaves et al (99), and Walpita et al (310). Since then, many other studies that involve centrifugation or the immune staining of centrifuged cultures for the rapid detection of HSV have been published (19,22,42,48 (244) found no increase in sensitivity for HSV detection after immunoperoxidase staining of centrifuged mink lung shell vial cultures versus immune staining of noncentrifuged cultures. Peterson et al (218) and others (254,328,329) have reported that shell vials or 24-well plates that were centrifuged and then stained 16 to 24 h postinoculation were less sensitive for HSV detection than conventional cell culture methods.…”
Section: Centrifugationmentioning
confidence: 99%